Pengaruh Edukasi Menggunakan Media Booklet Terhadap Persepsi Remaja Tentang Pencegahan Depresi (Window of Public Health Journal, 2026)
Depression is one of the most common mental health disorders among adolescents and may negatively affect academic performance, social relationships, and quality of life. Limited understanding and inadequate perceptions regarding depression can hinder early prevention efforts. Educational booklets may serve as an effective medium to improve adolescents’ awareness and perceptions of depression prevention. To determine the impact of educational booklets on improving adolescents’ perceptions of depression prevention at Madrasah Aliyah Muhammadiyah Sengkang, Wajo Regency. This study employed a quasi-experimental design using a one-group pretest-posttest approach. The study population consisted of 50 students, with 33 respondents selected through purposive sampling. Data were collected using perception questionnaires administered before and after the educational intervention. Data analysis was conducted using Paired Sample t-Test and simple linear regression with a significance level of 95%. Results: Prior to the intervention, most respondents demonstrated moderate perceptions (51.5%), while 24.2% showed high perceptions. Following the educational intervention, the proportion of respondents with high perceptions increased to 69.7%, and no respondents remained in the low-perception category. Simple linear regression analysis showed a significant effect of booklet-based education on adolescents’ perceptions regarding depression prevention (p=0.007). Educational booklets effectively improved adolescents’ perceptions regarding depression prevention and may be utilized as an alternative health promotion medium in school settings.